Immune checkpoint inhibitors in patients with solid tumors and poor performance status: A prospective data from the real-world settings. Issue 13 (2nd April 2021) - Kapoor, Akhil; Noronha, Vanita; Patil, Vijay M.; Menon, Nandini; Joshi, Amit; Abraham, George; Prabhash, Kumar
Abstract : Abstract: Immune checkpoint inhibitors (ICIs) are rapidly being incorporated as treatment option either alone or in combination with chemotherapy in most of the solid tumors. Since there is very limited data of ICI in patients with poor performance status (PS) from the real world settings, we performed a retrospective audit of patients who received ICI and report the analysis based on ECOG PS of these patients. This study is a retrospective audit of a prospectively collected database of patients receiving ICIs for advanced solid tumors in any line between August 2015 and November 2018 at Tata Memorial Hospital, Mumbai, India. All statistical calculations were performed using SPSS statistical software for windows version 20.0. A total of 155 patients who received ICIs during the specified period were evaluated for this study. Baseline ECOG PS 0–1 (n = 103, 66.4%) patients was associated with median OS 9.1 (95% CI [confidence interval], 4.4-NR) months when compared to ECOG 2–4 (n = 52, 33.5%) which had a median OS of 2.9 (95% CI; 1.8–5.5) months (HR, 1.7, 95% CI, 1.1–2.7, log rank P  = .017). The disease control rate for the poor PS group was 34.6%. However, 27.3% patients (95% CI: 20.3–34.3) were still alive at 1 year. Median OS in patients with PS 2 was 3.7 months (95% CI: 0–11.6) as compared to 1.8 months (95% CI: 0.2–3.4) for those with PS 3–4 (HR-2.0; 95% CI: 1.0–3.9, P  = .041). The tolerance to ICIs was good with no grade 3/4 toxicities in 44 (84.6%) patients. Immune checkpoint inhibitors are a safe and effective therapeutic option even in solid tumor patients with poor performance status.